Estimation of gross-structure parameters of giant dipole resonance: 2. Experimental testing - Dikiy, N.P.; Zakharchenko, A.A.; Lyashko, Yu.V.; Uvarov, V.L.; Shevchenko, V.A.; Tenishev, A.Eh. (Вопросы атомной науки и техники, 2021)
Experimental testing of a novel technique for determination of width and maximum of excitation function of a photonuclear reaction with dominant giant dipole resonance is conducted. The method is based on measurement of normalized reaction yield in a thin target, overlapping entirely a flux of X-rays and on processing of data obtained with the use of a developed analytical model. For the checking of method, the nickel and molybdenum foils of natural isotopic composition were activated by bremsstrahlung radiation at four energies of the electron beam in the range 40…95 MeV. The obtained parameters of cross-section of the reference reactions ⁵⁸Ni(γ,n)⁵⁷Ni and ¹⁰⁰Mo(γ,n)⁹⁹Mo are in good agreement with those presented in the available databases.